The Barriers of Foriegn Hotels Entering the Chinese Market - CHEN, LI-YIN (2006)
China is a late comer in the tourism industry, but it does not mean that China has lower development in the hotel industry because of its surprising growth in the number of hotel. Because the rapidly increasing international and domestic tourists, the Chinese blooming economy and many important international and continental events which will be held in China, the Chinese hotel industry has rapid development in China. Therefore, both foreign and domestic hotel corporations have been expanded their business to this potential market.